Problematika Pendidikan Agama Islam pada Anak dalam Keluarga Perkawinan Beda Agama di Caturtunggal Depok Sleman Yogyakarta - Muhammad Yusuf; Ani Susilawati; Aprezo Pardodi Maba (Indonesian Journal of Islamic Education Studies (IJIES), 2020)
This research is motivated by the reality of religious education for children in interfaith marriages. Where many problems are faced by parents in directing children's religious education. In order to make a focus discussion, the authors directed the study to an Islamic education. This study aims to obtain a detailed description of Islamic religious education for children in families with interfaith marriages at the Caturtunggal Depok, Sleman, Yogyakarta, as well as to discover their problems when applied Islamic education to their child. There are two stages of this study, the data collection and the data analysis. The data collection stage uses the method of observation, interviews, and documentation. While the data analysis uses a taxonomic method, an analysis carried out to explore more deeply Islamic education for children in families of interfaith marriages. The results of the study indicate that the problem in the application of Islamic education to children are parents too busy, limited religious knowledge, and parents did not make agreements on their children's religion. While the problems faced by children are confusion, inferiority, and apathy. In addition, there are positive aspects that can be taken from interfaith marriages, namely children have a basic knowledge of comparative religion and children become more tolerant in viewing religious differences.